Marketing and IT capability as mediators: The role of digital marketing and orientation on SMEs marketing performance (International Journal of Management and Sustainability, 2024)
The aim of this research is to examine the correlation linking digital marketing and the digital sphere orientation on marketing performance of MSMEs in Indonesia. Then, how information technology capabilities and marketing capabilities can be mediating variables between these three variables. This research uses a quantitative approach. This research falls under the category of exploratory research. The population in this study was 2,766; the research sample came from 338 MSMEs that are Go-Food partners spread across 4 districts on the island of Madura, Indonesia. The findings of the study indicate that digital marketing and digital orientation significantly influence the marketing performance of MSMEs. Information technology and marketing capabilities can be mediating and are variables that support other variables. The impact of this research is practical for Small and Medium Enterprises because, by improving marketing performance, they can maximize and develop their marketing capabilities. Information technology and marketing capability are widely used in research involving large companies. This research brings information technology capability within the scope of MSMEs because digital marketing has been widely applied to improve marketing performance. Then, this research has a practical implication to contribute to the role of information technology and marketing capability to answer how digital marketing impacts marketing performance.